Pengaruh Antara Social Comparison terhadap Body Dissatisfaction pada Mahasiswi Pengguna Instagram di Program Studi Profesi Psikolog Fakultas Psikologi Universitas Airlangga - Agustin, Desti; Prihastuti, Prihastuti; Andriani, Fitri (Universitas Nusantara PGRI Kediri, 2025)
This study aims to identify the influence of social comparison on body dissatisfaction among female students who use Instagram in the Professional Psychology Program at the Faculty of Psychology, Universitas Airlangga. The instruments used were the Social Comparison Scale adapted from O’Brien and the Body Dissatisfaction Scale based on the aspects defined by Rosen & Reiter. This research employed a quantitative approach with a survey method involving 54 respondents, selected using total sampling. Data analysis was conducted using simple linear regression with SPSS version 16.0. The results showed that social comparison did not have a significant effect on body dissatisfaction (p > 0.05). These findings indicate that social comparison is not a primary factor influencing body dissatisfaction among social media users in this study. The results highlight the importance of considering other components, such as self-esteem and coping mechanisms, when discussing body dissatisfaction among social media users.